Evaluation of Perinatal Outcomes in Pregnant Women With Low Amniotic Fluid Index - Forozan Milani; Leila khosousi; Seyedeh Hajar Sharami; Maryam Shakiba; Javid Rasoulian; Seyedeh Maryam Attari; Yalda Donyaei-Mobarrez (Tehran University of Medical Sciences, 2023)
Objective: The outcomes and management of low amniotic fluid index (AFI) in pregnancy are controversial. The purpose of this study was to determine the relationship between low AFI and perinatal outcomes. Materials and methods: This prospective study was conducted on 420 uncomplicated singleton pregnant women with a gestational age of over 28 weeks who referred to Al-Zahra Hospital in Rasht (Iran) for routine perinatal care. Pregnant women were divided into 3 groups of 140 patients based on the AFI and were followed up until delivery. Three groups included normal (8<AFI≤25 cm(, borderline )5<AFI≤8 cm( and oligohydramnios (AFI≤5cm) AFI. Results: The three adverse outcomes of respiratory distress, hospitalization in NICU, and length of hospitalization were statistically significantly different between the two groups with normal and borderline AFI and in the borderline group was more than the normal group. Adverse outcomes including; low birth weight (LBW), small for gestational age (SGA), respiratory distress, 1- min APGAR scores<7, hospitalization in NICU and its duration were statistically significantly different between the two groups with normal AFI and oligohydramnios, and it was more in the oligohydramnios group than the normal group. The three adverse outcomes of LBW, SGA and1- min APGAR scores<7 in the two borderline and oligohydramnios groups had statistically significant differences and were more in the oligohydramnios group than the borderline group. Conclusion: Consideration to the AFI in perinatal care to predict adverse perinatal outcomes and perform necessary interventions to improve these outcomes is necessary.